From Atom to Bit: The Ontology and Epistemology of Music in the Transition of Record Labels from Physical Media to Streaming - Ahmad Budi Sulistioyuwono; Isniar Budiarti; Siti Kurnia Rahayu; Dedi Sulistyo (Journal of World Science, 2026)
This conceptual study explores the ontological and epistemological transformation of music as the recording industry shifts from physical formats (atom) to digital streaming platforms (bit). Ontologically, music is no longer a tangible object but exists as infinite, immaterial data streams governed by algorithmic circulation. Epistemologically, knowledge about music, its value, popularity, and legitimacy, is increasingly constructed through datafication and platform-driven metrics. These dual transformations reshape the role of record labels: from centralized distributors of physical goods to curators and data analysts within a platformized ecosystem. Drawing on global trends with contextual insights from Indonesia, this research highlights how the convergence of digital ontology and computational epistemology alters not only the nature of music but also the institutional logic of its production and dissemination.